Nostalgiczny uśmiech. Autobiograficzny film Mateja Bobrika Self(less) Portrait - Mąka-Malatyńska, Katarzyna (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2012)
A Nostalgic Smile. Autobiography in the Documentary Film Etude Self(less) Portrait by Matej Bobrik The auto-documentary has a very short tradition in Polish cinema. The first films of this type were produced in Poland in the 1990s, when students of the National Film School in Łódź started making short films about themselves. In my essay, I focus on one such film, Self(less) Portrait, made by Matej Bobrik in 2012. The film tells the story of two young people: she is from Japan; he is from Slovakia and is the film’s director. They both studied film directing at the NFS in Łódź, and now live together in Warsaw. In the film, Bobrik shows the difficult relationship that exists between the two characters and members of their families, who live far away. It is a story about closeness, endearment, loneliness and death. In Self(less) Portrait, seriousness, sadness and nostalgia meet with humour and the grotesque. The article concentrates on the construction of the film, and the use of symbolism and humor in it. This is an exceptional film in contemporary Polish cinema because Bobrik does not engage in self-therapy – he does not accuse or talk about traumatic experiences, as Marcin Koszałka or Paweł Jóźwiak-Rodan do in their auto-documentaries.